THE SYMPHONY OF NATIONALISM: A POSTCOLONIAL STUDY TO THE MUSIC AND LYRICS OF INDONESIAN KERONCONG - Assiddiqi, Hasbi; Nurrachman, Dian; Priyawan, Pepen; Sudarisman, Yoga (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2025)
This paper examines the role of keroncong music as a medium for building and strengthening the values of patriotism, nationalism, and diversity harmony in Indonesia. Keroncong music, which was first introduced by Portuguese sailors in the 16th century, underwent a process of acculturation until it became an integral part of Indonesian cultural identity. During the colonial period, this genre of music was used as a symbolic tool of resistance that ignited the spirit of struggle and nationalism. With its touching lyrics and melodious tunes, keroncong became a means for the Indonesian people to express their love for their homeland and national identity. Songs such as “Bengawan Solo,” “Melati di Tapal Batas,” and “Rayuan Pulau Kelapa” became powerful symbols of patriotism and played an important role in the Indonesian independence movement. Postcolonial literary criticism was applied to understand how colonial and nationalist elements interacted in keroncong music, as well as how keroncong helped reconstruct postcolonial national identity in Indonesia. The results of the study show that keroncong music not only serves as entertainment but also as a symbol of struggle that reflects Indonesia's national identity. As an adaptive form of music, keroncong has successfully maintained its relevance by incorporating local elements and themes that reflect Indonesia's socio-political dynamics. In its lyrics, keroncong conveys messages rich in national values and diversity, capable of embracing all layers of Indonesian society, from various ethnicities, religions, and social backgrounds. The value of patriotism in keroncong music emerges through themes of struggle, love for the homeland, and pride as an independent nation. Nationalism in keroncong is further strengthened by the use of local language and idioms, as well as the incorporation of traditional cultural elements deeply rooted in Indonesian society.